Campur Kode pada Novel KKN (Kuliah Kerja Ngebaper) Karya Nurul Vidya Utami - Shintia Wulandari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to enable researchers to describe the types of code mixing contained in the KKN Novel (Kuliah Kerja Ngebaper) created by Nurul Vidya Utama. The researcher conducted the study using a qualitative method accompanied by a qualitative descriptive approach. Meanwhile, the method of collecting information and data used a direct method in the form of dialogue analysis in the related novel. The researcher himself acted as the data collection instrument. In addition to the data notebook, the main instrument used in this study was the researcher himself. Through the results of the analysis obtained in the KKN novel (Kuliah Kerja Ngebaper) which included the combination of elements in the form of 25 words, the combination of elements in the form of 18 phrases, the combination of elements in the form of 8 basters, the combination of elements in the form of 1 repetition, and the combination of elements in the form of 1 idiom. Knowing that there are two types of code mixing, which are external and internal code mixing. English, Japanese, Mandarin, and Arabic are classified as external code mixing. While Betawi, Sundanese, and Dawan Amanuban languages are included in languages that experience code mixing. The code-mixing order itself can be divided into three, namely adjectives, nouns, and verbs. It is hoped that in the future researchers can be an alternative reference for subsequent research in the field of sociolinguistics, especially for campus studies of literary greeting codes.